Microenvironmental Regulation of Chondrocyte Plasticity in Endochondral Repair—A New Frontier for Developmental Engineering - Wong, Sarah A.; Rivera, Kevin O.; Miclau, Theodore; Alsberg, Eben; Marcucio, Ralph S.; Bahney, Chelsea S. (Frontiers in Bioengineering and Biotechnology, 2018)
The majority of fractures heal through the process of endochondral ossification, in which a cartilage intermediate forms between the fractured bone ends and is gradually replaced with bone. Recent studies have provided genetic evidence demonstrating that a significant portion of callus chondrocytes transform into osteoblasts that derive the new bone. This evidence has opened a new field of research aimed at identifying the regulatory mechanisms that govern chondrocyte transformation in the hope of developing improved fracture therapies. In this article, we review known and candidate molecular pathways that may stimulate chondrocyte-to-osteoblast transformation during endochondral fracture repair. We also examine additional extrinsic factors that may play a role in modulating chondrocyte and osteoblast fate during fracture healing such as angiogenesis and mineralization of the extracellular matrix. Taken together the mechanisms reviewed here demonstrate the promising potential of using developmental engineering to design therapeutic approaches that activate endogenous healing pathways to stimulate fracture repair.